A new visual tool to improve the effectiveness of teaching and learning CPU scheduling algorithms - Jbara, Yosef Hasan (AEECT : 2017 IEEE Jordan Conference on Applied Electrical Engineering and Computing Technologies : 11-13 October, 2017, The University of Jordan School of Engineering, Amman, Jordan, 2017)
CPU scheduling plays a vital role in Operating Systems for undergraduate students. Understanding the CPU scheduling concepts and algorithms will positively affect students' further study on the course. However, teaching and learning CPU scheduling algorithms using conventional lectures and textbooks is faced with difficulties by many teachers and students. First, textbooks illustrate the CPU scheduling algorithms in an incomplete and unclear manner. Second, students solve problems manually. They don't receive any immediate feedback on their solutions. Third, due to time restriction, the teacher has to select a few small problems. To overcome these problems, we developed a simple visual educational simulator, which can be used as an efficient tool for teaching and learning CPU scheduling algorithms for one processor. Although this simulation tool is similar to others, it has its own unique features. In this paper, the educational impact, functional capabilities and features for this simulator are discussed in details.